Phosphorous antioxidants against polypropylene thermal degradation during rotational molding‐kinetic modeling. Issue 3 (11th August 2014) - Sarrabi, Salah; Lacrampe, Marie‐France; Krawczak, Patricia
ABSTRACT Phosphorous antioxidants efficiency against molten polypropylene (PP) thermal oxidation was assessed during isothermal ageing and processing by rotational molding. During isothermal ageing, experimental data were compared to the ones calculated on the basis of a kinetic model. Phosphonite is more effective than phosphite. Both phosphite and phosphonite decompose hydroperoxide and prevent initiation of oxidation reactions. However, phosphonite hydrolysis product acts as a radical chain terminator and blocks propagation reactions. Kinetic constants of stabilization reactions were evaluated and discussed. Further, this kinetic modeling was coupled to a thermal software, able to predict polymer temperature evolution during rotational molding and the degradation critical temperature (DCT) of different stabilized PP. A DCT of 235°C was obtained for PP stabilized with phosphonite and hindered phenol against 215°C for PP stabilized with phosphite and the same phenol. This difference of 20°C, corresponding to 5 min more heating is significant to optimize rotational molding. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41285.